Role of visible light on skin melanocytes: a systematic review - Chauhan, Aparna; Gretz, Norbert (Photochemistry and photobiology, 2021)
In the last few years, the focus of phototherapy has shifted toward the visible (400-700 nm) part of the electromagnetic spectrum of light. Lately, it has been demonstrated that visible light (VL) can have both beneficial and detrimental effects, especially on the skin. Previously and until now, the most harmful effects on the skin are associated with ultraviolet radiation (UVR). After exposure to natural light, the most evident and immediate change is observed on skin pigmentation. Various wavelengths within the visible spectrum have been reported to alter skin pigmentation. However, the underlying mechanisms are incompletely understood so far. The article aims to shed light on the progress made in the photobiology field (photobiomodulation, PBM) to study the role of visible light on skin melanocytes.